KESULITAN DAN SOLUSI PEMBELAJARAN ENGLISH READING TEXT - Dewi Kustanti (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2016)
The activity in teaching learning process is a main activity   in education.  Whatever that  is programmed will be carried in teaching learning process. Teaching learning process will determine its purpose. As an educator or coach, he/she    must give attention to individual difference in biology aspect, intellectual and physiological aspect.  Those   aspects will make close relationship between an educator and a learner. Therefore, in learning English Reading Text, it will be effective if all components in teaching learning process are included. Components in learning are: method, material of learning, tool/ aid of learning, purpose, teacher/ educator,  student/ learner. The purpose of reading is an effective reading, but it is at last forgotten by the learner and the student will face many difficult words  in reading. To get an effective reading the learner must get main idea   from that passage / text. As an educator or coach by digging or understanding student’s difficulties  in learning English Reading Text and doing  treatment  to get their solutions, he/she must  make a good program to get good  way  in teaching  reading and the learner will enjoy learning English, especially  for Reading.